Inflation and Unemployment in a Monetary Union - Carlberg, Michael (Springer Berlin Heidelberg : Imprint: Springer, 2008)
This book studies the coexistence of inflation and unemployment in a monetary union. The focus is on how to reduce the associated loss. The primary target of the European central bank is low inflation in Europe. The primary target of the German government is low unemployment in Germany. And the primary target of the French government is low unemployment in France. The European central bank has a quadratic loss function. The same applies to the German government and the French government. The key questions are: To what extent can the sequential process of monetary and fiscal decisions reduce the loss caused by inflation and unemployment? Is monetary and fiscal cooperation superior to the sequential process of monetary and fiscal decisions?